2020
DOI: 10.1177/1941738119886593
|View full text |Cite
|
Sign up to set email alerts
|

Is the Landing Error Scoring System Reliable and Valid? A Systematic Review

Abstract: Context: The Landing Error Scoring System (LESS) is a clinical tool often used in research and practice to identify athletes presenting high injury-risk biomechanical patterns during a jump-landing task. Objective: To systematically review the literature addressing the psychometric properties of the LESS. Data Sources: Three electronic databases (PubMed, Web of Science, and Scopus) were searched on March 28, 2018, using the term “Landing Error Scoring System.” Study Selection: All studies using the LESS as mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 50 publications
0
54
1
2
Order By: Relevance
“…The test demonstrates acceptable reliability and validity [10,11,23], as well as predictive value for non-contact ACL injury using a threshold of 5 errors [12]. The inter-rater reliability of the total LESS score is good to excellent, with ICC ranging from 0.83 to 0.92 [10,11,23] and typical errors at 0.71 LESS errors [10]. The results from the current study indicate that the typical errors from the automated processing and scoring of the LESS through computer vision when applying the random forest model (Table 2) are less than half an error greater than scores taken from two expert clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test demonstrates acceptable reliability and validity [10,11,23], as well as predictive value for non-contact ACL injury using a threshold of 5 errors [12]. The inter-rater reliability of the total LESS score is good to excellent, with ICC ranging from 0.83 to 0.92 [10,11,23] and typical errors at 0.71 LESS errors [10]. The results from the current study indicate that the typical errors from the automated processing and scoring of the LESS through computer vision when applying the random forest model (Table 2) are less than half an error greater than scores taken from two expert clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The Landing Error Scoring System (LESS) is one movement screen with demonstrated reliability [10,11] and validity [11,12]. Clinicians evaluate 2D video recordings from three double-leg drop-jump landing tasks per individual to detect 'movement errors' linked to non-contact anterior cruciate ligament (ACL) and other lower-extremity injury mechanisms [10].…”
Section: Of 13mentioning
confidence: 99%
“…A subjective assessment of the quality of movement between initial ground contact and peak knee flexion is also considered during LESS scoring. The scientific literature and clinical community use a range of terminology to describe the jump-landing task used to score the LESS, including jumplanding [2][3][4][5] , drop-jump 6 , drop-landing 7 , and drop-vertical jump [8][9][10] . Given that the jumplanding task of the original LESS is fundamentally active in nature (i.e., requires an individual to jump forward) 1 , in contrast to the more passive nature of the drop jump task, the term jump-landing will be used to reference the jump-landing task of the LESS.…”
Section: Introductionmentioning
confidence: 99%
“…The LESS scores range from 0 to 17 errors, where a greater score indicates a greater number of landing errors, poorer landing biomechanics, and greater risk of sustaining non-contact ACL injury. A recent systematic review concluded that the LESS is a valid and reliable screening tool, however the predictive values of the LESS for ACL injury remains uncertain based on current scientific evidence 5 . More specifically, Padua et al 11 evaluated ACL injury risk in elite-youth soccer players in a prospective study and concluded that LESS scoring has a good sensitivity (86%) and acceptable specificity (64%) in identifying risk of non-contact ACL injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation